Synthesis of 4H/fcc-Au@Metal Sulfide Core–Shell Nanoribbons - Fan, Zhanxi (2017)
Although great advances on the synthesis of Au–semiconductor heteronanostructures have been achieved, the crystal structure of Au components is limited to the common face-centered cubic (fcc) phase. Herein, we report the synthesis of 4H/fcc-Au@Ag2S core–shell nanoribbon (NRB) heterostructures from the 4H/fcc Au@Ag NRBs via the sulfurization of Ag. Remarkably, the obtained 4H/fcc-Au@Ag2S NRBs can be further converted to a novel class of 4H/fcc-Au@metal sulfide core–shell NRB heterostructures, referred to as 4H/fcc-Au@MS (M = Cd, Pb or Zn), through the cation exchange. We believe that these novel 4H/fcc-Au@metal sulfide NRB heteronanostructures may show some promising applications in catalysis, surface enhanced Raman scattering, solar cells, photothermal therapy, etc.